Use of bisphosphonates in a retrospective case series of children and adolescents with complex regional pain syndrome. Issue 8 (3rd June 2021) - Walfish, Laurel; Sbrocchi, Anne Marie; Rivera, Gonzalo; Ricaurte Gracia, Y Laura Nathaly; Mohamed, Nada; González Cárdenas, Víctor Hugo; Stoopler, Michelle; Ingelmo, Pablo
Abstract: Background: There is increasing evidence for the use of bisphosphonates to treat Complex Regional Pain Syndrome in adults. However, there are scarce data for their use in children with Complex Regional Pain Syndrome. Aim: This retrospective case series aimed to analyze the effects of intravenous bisphosphonate use in children and adolescents with Complex Regional Pain Syndrome enrolled in a multidimensional pain treatment program. Methods: We analyzed the data of 16 patients (15 females and 1 male, mean age 14 ± 3 years) who received infusions of zoledronic acid (0.015 ± 0.0044mg/kg), pamidronate (0.72 ± 0.17mg/kg), or both depending on their initial response between October 2014 and December 2019. The primary endpoint of the study was the patient's global impression of change. Secondary outcomes included pain intensity, physical function, role function (school attendance), need for pain medications, and adverse effects. Results: Nine of 16 patients reported meaningful improvements (global impressions of change of 84% or higher) at a median follow‐up time of 16 (8–21) months after their last infusion of bisphosphonates. There were also meaningful reductions in pain intensity and the need for pain medications. There was an increase in the proportion of patients with minimal or without physical disability, and almost all patients normalized their school activities. Thirteen patients (81%) reported adverse effects, mostly flu‐like symptoms, for a few days after the infusion. Conclusion: The use of bisphosphonate infusions may represent an effective treatment option for children with Complex Regional Pain Syndrome, not responding to multidisciplinary pain treatment programs.